summary |
shortlog |
changelog |
graph |
tags |
bookmarks |
branches |
files |
changeset |
file |
latest |
revisions |
annotate |
diff |
comparison |
raw |
help

src/Sequents/T.thy

author | wenzelm |

Sat, 14 Dec 2013 17:28:05 +0100 | |

changeset 54742 | 7a86358a3c0b |

parent 51309 | 473303ef6e34 |

child 60770 | 240563fbf41d |

permissions | -rw-r--r-- |

proper context for basic Simplifier operations: rewrite_rule, rewrite_goals_rule, rewrite_goals_tac etc.;
clarified tool context in some boundary cases;

(* Title: Sequents/T.thy Author: Martin Coen Copyright 1991 University of Cambridge *) theory T imports Modal0 begin axiomatization where (* Definition of the star operation using a set of Horn clauses *) (* For system T: gamma * == {P | []P : gamma} *) (* delta * == {P | <>P : delta} *) lstar0: "|L>" and lstar1: "$G |L> $H ==> []P, $G |L> P, $H" and lstar2: "$G |L> $H ==> P, $G |L> $H" and rstar0: "|R>" and rstar1: "$G |R> $H ==> <>P, $G |R> P, $H" and rstar2: "$G |R> $H ==> P, $G |R> $H" and (* Rules for [] and <> *) boxR: "[| $E |L> $E'; $F |R> $F'; $G |R> $G'; $E' |- $F', P, $G'|] ==> $E |- $F, []P, $G" and boxL: "$E, P, $F |- $G ==> $E, []P, $F |- $G" and diaR: "$E |- $F, P, $G ==> $E |- $F, <>P, $G" and diaL: "[| $E |L> $E'; $F |L> $F'; $G |R> $G'; $E', P, $F'|- $G'|] ==> $E, <>P, $F |- $G" ML {* structure T_Prover = Modal_ProverFun ( val rewrite_rls = @{thms rewrite_rls} val safe_rls = @{thms safe_rls} val unsafe_rls = @{thms unsafe_rls} @ [@{thm boxR}, @{thm diaL}] val bound_rls = @{thms bound_rls} @ [@{thm boxL}, @{thm diaR}] val aside_rls = [@{thm lstar0}, @{thm lstar1}, @{thm lstar2}, @{thm rstar0}, @{thm rstar1}, @{thm rstar2}] ) *} method_setup T_solve = {* Scan.succeed (fn ctxt => SIMPLE_METHOD (T_Prover.solve_tac ctxt 2)) *} (* Theorems of system T from Hughes and Cresswell and Hailpern, LNCS 129 *) lemma "|- []P --> P" by T_solve lemma "|- [](P-->Q) --> ([]P-->[]Q)" by T_solve (* normality*) lemma "|- (P--<Q) --> []P --> []Q" by T_solve lemma "|- P --> <>P" by T_solve lemma "|- [](P & Q) <-> []P & []Q" by T_solve lemma "|- <>(P | Q) <-> <>P | <>Q" by T_solve lemma "|- [](P<->Q) <-> (P>-<Q)" by T_solve lemma "|- <>(P-->Q) <-> ([]P--><>Q)" by T_solve lemma "|- []P <-> ~<>(~P)" by T_solve lemma "|- [](~P) <-> ~<>P" by T_solve lemma "|- ~[]P <-> <>(~P)" by T_solve lemma "|- [][]P <-> ~<><>(~P)" by T_solve lemma "|- ~<>(P | Q) <-> ~<>P & ~<>Q" by T_solve lemma "|- []P | []Q --> [](P | Q)" by T_solve lemma "|- <>(P & Q) --> <>P & <>Q" by T_solve lemma "|- [](P | Q) --> []P | <>Q" by T_solve lemma "|- <>P & []Q --> <>(P & Q)" by T_solve lemma "|- [](P | Q) --> <>P | []Q" by T_solve lemma "|- <>(P-->(Q & R)) --> ([]P --> <>Q) & ([]P--><>R)" by T_solve lemma "|- (P--<Q) & (Q--<R) --> (P--<R)" by T_solve lemma "|- []P --> <>Q --> <>(P & Q)" by T_solve end